If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (11 + 8i) + -1(5 + 4i) = 0 Remove parenthesis around (11 + 8i) 11 + 8i + -1(5 + 4i) = 0 11 + 8i + (5 * -1 + 4i * -1) = 0 11 + 8i + (-5 + -4i) = 0 Reorder the terms: 11 + -5 + 8i + -4i = 0 Combine like terms: 11 + -5 = 6 6 + 8i + -4i = 0 Combine like terms: 8i + -4i = 4i 6 + 4i = 0 Solving 6 + 4i = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 4i = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 4i = 0 + -6 4i = 0 + -6 Combine like terms: 0 + -6 = -6 4i = -6 Divide each side by '4'. i = -1.5 Simplifying i = -1.5
| 1/5[x-5]-4=2 | | 15-5t=-5(t-3) | | 2(8s-7)= | | 2(d-6)-(-3)=9 | | 12s-8+4s-6= | | 3y+x-2=0 | | 20-9w=4(15-1) | | r+20r+r+20r= | | 12-y/2=8 | | 4(4a-8)+6a= | | -5[4y-11]-3=12 | | 8(2x+10)-12= | | 4(x+6)-2= | | 4d+1=2d+15 | | n+n+6n+6n= | | a+3a+a+3a= | | 5(x-4)=-15 | | 2[6-2x]-1=7 | | 8a+72=106.4 | | (2x-3)(4x+3)= | | 9x-5(x-2)=6 | | 4x^3-12x^2-52x+60=0 | | 5y-8=y-24 | | 19.2=6c-3 | | 7s+6y-3s+4y+15= | | (5+9i)+(3-2i)= | | 5x-6=2x+10 | | ln(7x-13)=ln(2x-17) | | 4=k+17 | | 3(a+1)-5=2a-7 | | -2[y-7]+18=8 | | x^2-95=-94 |